Implementation of Local Wisdom-Based Storybooks in Improving Creative Character and Love for the Country of Elementary School Students - Hulaipah, Atikatul; Iffat Nabilah, Muna; Nafisah, Nur; Khairina, Dita; Bayan Purwadi, Lalu; Sumardi, Lalu; Setiadi, Dadi (Lafadz Jaya Publisher, 2024)
This study was motivated by the lack of age-appropriate reading materials at the school, as well as the teacher's desire to invite students to preserve local culture through local languages. This study aims to describe the implementation of the P5 storybook program with the theme of local wisdom in fostering the creative character and love for the country of grade IV students of SDN 3 Beleka. Using a descriptive case study approach, the subject of this research is the fourth grade teacher of SDN 3 Beleka. Data were collected through interviews and documentation. The results of the research on the implementation of the Pancasila Student Profile Strengthening Project (P5) through the Storybook program show that this initiative increases the creativity and sense of patriotism of grade IV students of SDN 3 Beleka. The implementation of the P5 program through Storybooks includes three main stages: planning, implementation, and evaluation. The impact of the P5 storybook program is proven to increase students' creativity which can be seen from two aspects, namely creativity in ideas and presentation, as well as the development of writing and speaking skills. Meanwhile, the impact of the Storybook P5 program on the character of patriotism is reflected in two main results, namely fostering a love for local culture and deepening students' understanding of local identity.